Estimating abundance of Eastern Canada-West Greenland bowhead whales using genetic mark-recapture analyses - Biddlecombe, Brooke A.; Ferguson, Steven H.; Heide-Jørgensen, Mads Peter; Gillis, Darren M.; Watt, Cortney A. (Global ecology and conservation, 2023)
The Eastern Canada-West Greenland (EC-WG) bowhead whale (Balaena mysticetus) population is widely distributed across the eastern Canadian Arctic and across Baffin Bay to the western coast of Greenland. Their vast distribution makes obtaining population estimates via aerial surveys difficult, as coverage over their entire range is not possible. Genetic mark recapture analyses address this issue, as biopsy samples can be collected at various locales across the EC-WG bowhead whale population’s distribution and microsatellites can be analyzed to identify unique individuals. EC-WG bowhead whales were subject to intense commercial whaling pressure between the early 1700 s and early 1900 s, after which a moratorium on commercial whaling was put in place in 1915. We used available genetic samples from EC-WG bowhead whales in mark recapture models to estimate population abundance from 2012 to 2021 to gain insight on population dynamics ∼100 years post commercial whaling. The preferred model, using a Jolly-Seber structure, estimated the total abundance as 5173 individuals (CI: 3436–7788). Since the cessation of commercial whaling, the population has been thought to be rebounding, which is reflected by gradually increasing abundance estimates, from the low hundreds in the 1970 s and 1980 s, to ∼6000 in the early 2000 s, but our present estimate suggests population abundance may be plateauing well below the pre-commercial whaling carrying capacity estimate. This population estimate for EC-WG bowhead whales is required to update the population dynamics for conservation efforts.